2009
DOI: 10.1007/s11661-009-0103-z
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Mechanisms in Nanocrystalline Materials

Abstract: As a result of recent investigations on nanocrystalline (nc) materials, extensive experimental data on the deformation behavior of these materials have become available. In this article, an analysis of these data was performed to identify the requirements that a viable deformation mechanism should meet in terms of accounting for the mechanical characteristics and trends that are revealed by the data. The results of the analysis show that a viable deformation mechanism is required to account for the following: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 46 publications
(120 reference statements)
0
15
0
Order By: Relevance
“…An analysis of experimental creep data reported for nc materials [15] has revealed that a successful deformation mechanism is required to account for account for: (a) deformation is rate dependent, (b) an activation volume that has a value in the range of 10 b 3 -20 b 3 , (b) an activation energy that is close to the activation energy for boundary diffusion but that decreases with increasing stress, (c) the magnitudes of deformation rates that cover wide ranges of temperatures, stresses, and grain sizes and (d) inverse…”
Section: The Present Communication Focuses On Examining the Creep Tramentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of experimental creep data reported for nc materials [15] has revealed that a successful deformation mechanism is required to account for account for: (a) deformation is rate dependent, (b) an activation volume that has a value in the range of 10 b 3 -20 b 3 , (b) an activation energy that is close to the activation energy for boundary diffusion but that decreases with increasing stress, (c) the magnitudes of deformation rates that cover wide ranges of temperatures, stresses, and grain sizes and (d) inverse…”
Section: The Present Communication Focuses On Examining the Creep Tramentioning
confidence: 99%
“…Consideration of several proposed rate-dependent mechanisms [16][17][18] in light of these requirements has shown [15] that the predictions of the model of dislocationaccommodated boundary sliding (DABS) [19] are consistent with the above requirements.…”
Section: The Present Communication Focuses On Examining the Creep Tramentioning
confidence: 99%
“…This mechanism is commensurate with the stress exponents seen in macroscale behavior reported in Sn-3.5Ag alloys. [7,13,34] In addition to the stress exponent, the more pronounced primary creep regime in the high stress step of Figure 3b is also indicative of dislocation-based mechanism. Work by Kerr and Chawla [10] showed a stress exponent of 4 at high temperatures where bulk diffusion is dominant and 6 at low temperatures where dislocation core diffusion is dominant.…”
Section: Resultsmentioning
confidence: 93%
“…The data show that the creep behavior cannot be explained by Equation (5), which is applicable to the description of superplasticity in micrograined and ultrafine grained materials for the following reasons: (a) ductility is very limited (less than 12 %); (b) the stress exponent is high and variable; (c) the grain size sensitivity is 3 not 2, and (d) an activation energy that is close to the activation energy for boundary diffusion but decreases with increasing applied stress. Although several mechanisms [22][23][24][25] were mentioned or developed to account for the deformation behavior of nc materials, it has been shown that the predictions of the model of dislocation-accommodated boundary sliding (DABS) [26] are consistent with the above characteristics.…”
Section: Superplasticity In Nanocrystalline Materialsmentioning
confidence: 99%
“…The basic concept used in developing the model of DABS [25,26] is that plasticity in nc-materials is the result of boundary sliding accommodated by the generation and motion of dislocations under local stresses, which are higher than applied stresses due to the development of stress concentrations. The model, unlike that of Ball and Hutchison [5] for superplasticity in micrograined materials, does not involve a dislocation pile-up at the opposite boundary of the grain blocking sliding.…”
Section: Superplasticity In Nanocrystalline Materialsmentioning
confidence: 99%